Pseudomonas aeruginosa population dynamics in a vancomycin-induced murine model of gastrointestinal carriage - Marine Lebrun-Corbin; Bettina H. Cheung; Karthik Hullahalli; Katherine G. Dailey; Keith Bailey; Matthew K. Waldor; Richard G. Wunderink; Kelly E. R. Bachta; Alan R. Hauser (mBio)
ABSTRACT Pseudomonas aeruginosa is a common nosocomial pathogen and a major cause of morbidity and mortality in hospitalized patients. Multiple reports highlight that P. aeruginosa gastrointestinal colonization may precede systemic infections by this pathogen. Gaining a deeper insight into the dynamics of P. aeruginosa gastrointestinal carriage is an essential step in managing gastrointestinal colonization and could contribute to preventing bacterial transmission and progression to systemic infection. Here, we present a clinically relevant mouse model relying on parenteral vancomycin pretreatment and a single orogastric gavage of a controlled dose of P. aeruginosa. Robust carriage was observed with multiple clinical isolates, and carriage persisted for up to 60 days. Histological and microbiological examination of mice indicated that this model indeed represented carriage and not infection. We then used a barcoded P. aeruginosa library along with the sequence tag-based analysis of microbial populations (STAMPR) analytic pipeline to quantify bacterial population dynamics and bottlenecks during the establishment of the gastrointestinal carriage. Analysis indicated that most of the P. aeruginosa population was rapidly eliminated in the stomach, but the few bacteria that moved to the small intestine and the cecum expanded rapidly. Hence, the stomach constitutes a significant barrier against gastrointestinal carriage of P. aeruginosa, which may have clinical implications for hospitalized patients.IMPORTANCEWhile Pseudomonas aeruginosa is rarely part of the normal human microbiome, carriage of the bacterium is quite frequent in hospitalized patients and residents of long-term care facilities. P. aeruginosa carriage is a precursor to infection. Options for treating infections caused by difficult-to-treat P. aeruginosa strains are dwindling, underscoring the urgency to better understand and impede pre-infection stages, such as colonization. Here, we use vancomycin-treated mice to model antibiotic-treated patients who become colonized with P. aeruginosa in their gastrointestinal tracts. We identify the stomach as a major barrier to the establishment of gastrointestinal carriage. These findings suggest that efforts to prevent gastrointestinal colonization should focus not only on judicious use of antibiotics but also on investigation into how the stomach eliminates orally ingested P. aeruginosa.